2018
DOI: 10.1159/000492628
|View full text |Cite
|
Sign up to set email alerts
|

Improved Prediction of Survival by a Risk Factor-Integrating Inflammatory Score in Sorafenib-Treated Hepatocellular Carcinoma

Abstract: <b><i>Background and Aims:</i></b> Inflammation affects progression of hepatocellular carcinoma (HCC). We therefore postulate that systemic inflammatory markers could help to predict prognosis in HCC patients receiving sorafenib therapy. <b><i>Methods:</i></b> Overall survival (OS) of HCC patients receiving palliative sorafenib treatment was correlated with the neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), C-reactive protein to albumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 44 publications
2
17
3
Order By: Relevance
“…Although a large literature already exists on the use of various common blood tests that reflect systemic inflammation and prognosis, and to a lesser extent reflecting in turn the extent of the disease [ [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] ], the precise relationship of inflammatory markers to tumor extent has not been well defined. The current work attempts to do this by use of the commonly used PLR and NLR ratios, to assess their relationship to MTD and to try to find their ability to predict small tumor size (MTD).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a large literature already exists on the use of various common blood tests that reflect systemic inflammation and prognosis, and to a lesser extent reflecting in turn the extent of the disease [ [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] ], the precise relationship of inflammatory markers to tumor extent has not been well defined. The current work attempts to do this by use of the commonly used PLR and NLR ratios, to assess their relationship to MTD and to try to find their ability to predict small tumor size (MTD).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation-based prognostic scores have been shown to be associated with survival [ 3 ] and with various parameters of tumor aggressiveness [ 4 ]. This may be related to the involvement in tumor growth of a variety of easily measurable indices of inflammation [ 5 ] in routine clinical blood tests, including levels of neutrophils, lymphocytes, monocytes, platelets, albumin, C-reactive protein (CRP), as well as marker ratios, such as albumin and CRP (Glasgow Index), neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) and monocyte-to-lymphocyte ratios, amongst others [ [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] ]. In the current study, NLR and PLR were evaluated with reference to maximum tumor diameter (MTD) and also to survival in a large Turkish HCC cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Mean survival was shorter if PLR ≥ 254 in our series. It is an evidence that either higher NLR or PLR were significantly asso-International Journal of Clinical Medicine ciated with lymph node metastasis, and poor overall survival in most studies [6] [38] [51]. Taken together, either increased neutrophil and platelet, or decreased lymphocyte will elevate either NLR or PLR.…”
Section: Discussionmentioning
confidence: 99%
“…Most oncologists try to get a good survival due to the improvement of care program in the world [2] [3]. Pretreatment imaging and assessment remain the main methods used to evaluate prognosis in liver cancer patients after treatments [4] [5] [6]. The relationship of the prognosis of HCC patients and inflammation was noted in recent decade [4] [7] [8].…”
Section: Introductionmentioning
confidence: 99%
“…The predictive role of serum inflammatory markers in cancer has been paid more and more attention. The prognostic value of serum inflammation indicators before treatment for liver cancer has been confirmed by studies focus on surgical resection, liver transplantation, target therapy, radiofrequency ablation (RFA),transcatheter arterial chemoembolization (TACE) and selective internal radiation therapy (SIRT) [16][17][18][19][20][21]. However, studies about cases of liver cancer treated with SBRT rarely reported prognostic inflammatory markers, instead, most of which merely focused on NLR and PLR [22].…”
Section: Introductionmentioning
confidence: 99%